A LOCAL CONFLICT AS A REFLECTION OF THE GOVERNMENT OF THE HISPANIC MONARCHY. THE DISPUTE BETWEEN THE GOVERNOR AND THE COMMISSIONER OF THE INQUISITION IN THE PHILIPPINES IN THE MID-SEVENTEENTH CENTURY. (Tzintzun, Revista de Estudios Históricos, 2023)
In 1668, the commissioner of the Inquisition in the Philippine Islands, José dePaternina, imprisoned and later sent Governor Diego de Salcedo to New Spain.After the conflict that this action generated, the Council of the Indies and theCouncil of the Supreme Inquisition had to intervene. The objective of this text isto review how the historiography analyzed the case and present some newconsiderations from the analysis of the file that contains the investigation carriedout by the Court of the Inquisition of Mexico. The hypothesis that is exposed isthat the form of government of the Hispanic Monarchy caused these conflictsamong its different government institutions and, at the same time, had the capacityto resolve them without actually causing major conflicts.
Keywords: Hispanic Monarchy; Philippines; New Spain; Inquisition; 17th century